Structural characteristics and mechanisms of fluorapatite mechanochemical synthesis - Jokanović Vukoman; Čolović Božana; Živković-Sandić Marija; Popović-Bajić Marijana; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2016)
This paper analyzes mechanisms of fluorapatite mechanochemical synthesis and its structural characteristics. Several studies of Jokanovic et al. published in appropriate journals and the book 'Nanomedicine, the biggest challenge of the 21st century' are the base for this article. Characteristics of obtained materials show numerous biological advantages associated with the specific structural design of material during the process of synthesis. X-ray diffraction (XRD) and infrared spectroscopy with Fourier transform (FTIR) were used for studying the processes of fluorapatite synthesis.